The Effectiveness of Human Resource Planning on the Administration Staff - Sufriadi, Sufriadi (SCAD Independent, 2017)
This research aimed to determine the planning arrangement, the implementation effectiveness and the efforts to overcome the obstacles in the planning and implementing human resource planning on the administration staff at the Faculty of Education and Teacher Training of UIN Ar-Raniry Banda Aceh. Administration and human resource management are the capital of the development in which the purpose of it is to gain the improvement in all aspects. Human resources are very valuable that require a serious planning when adopted into an organization. Human resources are known as a crucial component, recognized as a universal element in the organization effectiveness and a key to a competitive profit source. Besides giving an excellent service to the society, the task of human resources is to complete all the programs or the activities related to the government policies that affect human welfare in positive ways. The research used the qualitative method with case study design because the focus of this research was the specific phenomenon, the human resource planning on the staff administration.